2015
DOI: 10.1108/lodj-03-2014-0056
|View full text |Cite
|
Sign up to set email alerts
|

The effects of authentic leadership on turnover intention

Abstract: Purpose – The purpose of this paper is to examine the relationship between employees’ perception of authentic leadership and their turnover intention as mediated by employees’ work-group identification (WID) and work engagement. Design/methodology/approach – Structural equation modeling was used to analyze the data from 623 Spanish employees. Findings – Results show that authentic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 74 publications
5
72
0
6
Order By: Relevance
“…Head nurses‧ leadership styles influenced nurses‧ thoughts, attitudes, and perceptions of their work as well as their decisions to leave their jobs (Azanza et al, ). This study's results show that the nurses considered their head nurses to be frequently applying authentic leadership.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Head nurses‧ leadership styles influenced nurses‧ thoughts, attitudes, and perceptions of their work as well as their decisions to leave their jobs (Azanza et al, ). This study's results show that the nurses considered their head nurses to be frequently applying authentic leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Authentic leaders are aware of their thinking and behaviour and respect others‧ moral perspectives, knowledge, and strengths (Clapp‐Smith, Vogelgesang, & Avey, ). Authentic leadership can retain employees by creating trust and authentic relationships among members of the work group (Azanza, Moriano, Molero, & Mangin, ). The American Association of Critical‐Care Nurses () noted that authentic leadership was the key element in creating a good work environment in nursing practice.…”
Section: Theoretical Framework and Relevant Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies concentrate on the partnership in between transformational leadership to organizational commitment, job satisfaction, and organizational trust [17]; and moreover turnover intention [18]. This design of leadership emerges with multiple leadership behaviors.…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…Turnover intention is considered an antecedent of the actual behavior of leaving the organization, and many studies prove a strong correlation between turnover intentions and actual turnover behavior [23]. There has been a lot of research on the relationship between turnover intentions and various styles of leadership (e.g., [24][25][26]). For example, empirical findings by Gyensare et al [24] showed a positive association between transformational leadership and turnover intentions.…”
Section: El and Turnover Intentionmentioning
confidence: 99%